Postoperative Cavity Stereotactic Radiosurgery for Brain Metastases - Marchan, Eduardo M.; Peterson, Jennifer; Sio, Terence T.; Chaichana, Kaisorn L.; Harrell, Anna C.; Ruiz-Garcia, Henry; Mahajan, Anita; Brown, Paul D.; Trifiletti, Daniel M. (Frontiers in Oncology, 2018)
During the past decade, tumor bed stereotactic radiosurgery (SRS) after surgical resection has been increasingly utilized in the management of brain metastases. SRS has risen as an alternative to adjuvant whole brain radiation therapy (WBRT), which has been shown in several studies to be associated with increased neurotoxicity. Multiple recent articles have shown favorable local control rates compared to those of WBRT. Specifically, improvements in local control can be achieved by adding a 2 mm margin around the resection cavity. Risk factors that have been established as increasing the risk of local recurrence after resection include: subtotal resection, larger treatment volume, lower margin dose, and a long delay between surgery and SRS (>3 weeks). Moreover, consensus among experts in the field have established the importance of a) fusion of the pre-operative magnetic resonance imaging scan to aid in volume delineation b) contouring the entire surgical tract and c) expanding the target to include possible microscopic disease that may extend to meningeal or venous sinus territory. These strategies can minimize the risks of symptomatic radiation-induced injury and leptomeningeal dissemination after post-operative SRS. Emerging data has arisen suggesting that multifraction postoperative SRS, or alternatively, preoperative SRS could provide decreased rates of radiation necrosis and leptomeningeal disease. Future prospective randomized clinical trials comparing outcomes between these techniques are necessary in order to improve outcomes in these patients.